Language Planning in Preschool Education with "Annotated Bibliography." - Cazden, Courtney B. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
A discussion of language in preschool education reviews research findings on children's language acquisition and its relationship to their general development and examines issues to be considered in making decisions for each community and program. The first section summarizes basic knowledge about preschool language development, facilitating language development at this stage, and the specific language problems faced by multilingual preschool children at home and in group care. The second section looks more closely at the sociolinguistic dimensions affecting language choice and proficiency. In the next section, three preschool program descriptions are given, each involving a situation in which a higher-status national language coexists with an indigenous language. They include a Spanish-Quechua/Aymara transitional bilingual program (Peru), a Gaelic maintenance program in Scotland's Western Isles, and a Maori revitalization program (New Zealand). The fourth section discusses practical aspects of planning for language learning and emergent literacy in preschool environments, including group size and organization, adult-child relationships, choice of language, instructional materials, staffing and staff training, adult and community participation, and administration. A brief "conclusion" and a list of almost 100 references conclude this part of the document. A special feature of the "annotated bibliography" which follows is that the annotations are written around themes (countries/communities and language use at the preschool level) and are similar in nature to essay reviews. Entries are listed alphabetically by country and information is provided under the following headings: document source; community (including language situation); educational system specifics; program (including characteristics/components); and comments. (MSE)
Sponsoring Agency: International Development Research Centre, Ottawa (Ontario).
ERIC Note: Paper presented at the World Congress of Applied Linguistics sponsored by the International Association of Applied Linguistics (9th, Thessaloniki, Greece, April 15-21, 1990).
Educational level discussed: Preschool Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Annotated Bibliographies; Bilingual Education Programs; Caregivers; Case Studies; Child Language; Educational Environment; Emergent Literacy; Foreign Countries; Indigenous Populations; Irish; Language Acquisition; Language Maintenance; Language Planning; Language Proficiency; Language Role; Literacy Education; Multilingualism; Preschool Children; Preschool Education; Program Descriptions; Quechua; Sociolinguistics; Spanish; Transitional Programs; Uncommonly Taught Languages; Maori (Language) -- New Zealand -- Peru -- Scotland; Information Analyses; Reference Materials, Directories/Catalogs.; Speeches/Meeting Papers